(untitled) (Ustozlar uchun, 2025)
This article examines the pedagogical impact of teaching diverse literary genres—specifically thrillers and classic dramas—in academic lyceums. By conducting a comparative analysis, the research explores how genre diversity stimulates student engagement and enhances linguistic competence. Using Philip Prowse’s contemporary thrillers and classic storytelling techniques found in O. Henry and Agatha Christie, the study demonstrates that contrasting genres help students identify different narrative structures, stylistic devices, and thematic depths.